APLIKASI PENGOLAHAN DATA PASIEN STUDI KASUS RSUD SAWERIGADING PALOPO SULAWESI SELATAN - Abdul Haris; Alan Burhan (PETIR, 2015)
Currently the Hospital Sawerigading Palopo still using manual systems in data processinginpatients and outpatients, the data processing system are now experiencing difficulties in findingthe necessary patient data so it takes a long time. In addition the processing of patient data with thecurrent system does not have a good reporting system, so we need a new system, which canovercome these problems. Therefore, Sawerigading Regional General Hospital (HospitalSawerigading) require patient data processing applications that are capable of handling a varietyof obstacles above. Applications will facilitate the processing of patient data to hospital officials indata processing and printing patient reporting of patient data.